The features of complex therapy of bacterial vaginosis in pregnant women with cervical incompetence - Д. Г. Коньков; Н. В. Адамчук; В. В. Кливак (Publishing House TRILIST, 2020)
Objective of the study: to study the clinical and laboratory efficacy of the Femivag® (contains Lactobacillus gasseri, Lactobacillus rhamnosus) drug in the complex treatment of bacterial vaginosis (BV) in pregnant women with high risk of preterm birth. Materials and methods. 42 pregnant women at the 16-18 weeks of gestation with cervical dysfunction and BV diagnosed before cervical pessary installation were examined and treated. All patients were assessed the dynamics of symptoms severity, performed PCR testі with a quantitative count of opportunistic pathogens and Lactobacillus spp. Perinatal and neonatal outcomes were also assessed. Femivag® vaginal capsules were prescribed to 24 women (main group) to restore the vaginal microbiota after BV treatment. 18 pregnant women used dietary supplements containing pro- and prebiotics (comparison group). The examination was performed before treatment, 4 and 15-16 days from the therapy start, 4 and 8 weeks after treatment. Results. Vaginal probiotic Femivag® as a component of complex therapy of BV before the installation of cerclage pessary was more effective than the oral food supplements with pro- and prebiotics in terms of reducing in vaginal discharge and vaginal discomfort, the disappearance of vaginal itching and burning sensation for 4 days of therapy. Gardnerella vaginalis / Prevotella bivia / Porphyromonas spp., Mobiluncus spp. / Corynebacterium spp. and Atopobium vaginae disappeared and vaginal normobiota significant recovered in the second trimester in women with cervical dysfunction at 4 and 8 weeks from the start of BV treatment with Femivag®. Frequency of premature rupture of membranes and chorioamnionitis significantly decreased in the main group. Femivag® was well tolerated and had no side effects. Conclusions. Femivag® vaginal capsules had a pronounced clinical and laboratory effect in the complex treatment of BV in pregnant women with incompetent cervix